Analyzing vibration characteristics: a comparative study of laser vs. spindle systems - Farhan, Mohammed F.; Salman, Suhad D.; Leman, Z.; Alkbir, M. F.M.; Januddi, Fatihhi (Al-Nahrain University College of Engineering, 2025)
In the field of engineering, 3D printers are indispensable due to their high precision. This study focuses on the construction and optimization of a 3D printer using aluminum T-slotted bars for the frame, Raspberry Pi 4 for control, and Lightburn software for image printing and machine control. After assembling the main components and programming with Marlin firmware, the machine was tested for vibration and noise reduction. The research compared the vibration of a diode laser and spindle during printing, revealing significantly lower vibration with the laser compared to the spindle. These findings demonstrate the effectiveness of the constructed 3D printer in reducing vibration and noise during operation.